Prevalensi Kolonisasi Bakteri Methicillin-Resistant Staphylococcus aureus (MRSA) di Ruang Intensive Care Unit (ICU) Rumah Sakit Umum Daerah Abdul Moeloek Bandar Lampung - Hasril Mulya Budiman; Tri Umiana Soleha; Efrida Warganegara; Dwi Indria Anggraini (Majority, 2020)
Methicillin-Resistant Staphylococcus aureus (MRSA) is a bacterium Staphylococcus aureus which has a resistance to methicillin and some beta-lactam antibiotics. MRSA can colonize as normal flora in some parts of the human body, such as the nose, skin, hands, perineum, and other parts of the body. Intensive Care Unit (ICU) is the high risk areas for MRSA transmission. The purpose of this study was to determine the prevalence of MRSA in ICU of Regional General Hospital Abdul Moeloek Bandar Lampung. The method used in this study was cross sectional. The primary data used in this research were obtained by collecting a nasal and hand swab of patients treated in the ICU at one time and then identify the MRSA bacteria in laboratory to determine its prevalence. The results of bacterial identification on the nose and hand specimen showed 15 out of 40 samples tested positive for MRSA (37.50%). The results of the identification of bacteria MRSA shows the prevalence of MRSA colonization of the nose specimen at 17.50%, hand amounted to 32.50%, and which are both positive at 12.50%. Based on the research that has been done, it can be concluded there is a prevalence of colonization of the MRSA bacteria in ICU of Regional General Hospital Bandar Lampung Abdul Moeloek is 37.50%.